Human dental pulp stem cells expressing STRO‐1, c‐kit and CD34 markers in peripheral nerve regeneration. (2nd March 2017) - Carnevale, Gianluca; Pisciotta, Alessandra; Riccio, Massimo; Bertoni, Laura; De Biasi, Sara; Gibellini, Lara; Zordani, Alessio; Cavallini, Gian Maria; La Sala, Giovanni Battista; Bruzzesi, Giacomo; Ferrari, Adriano; Cossarizza, Andrea; et al.
Abstract: Peripheral nerve injuries are a commonly encountered clinical problem and often result in long‐term functional defects. The application of stem cells able to differentiate in Schwann cell‐like cells in vitro and in vivo, could represent an attractive therapeutic approach for the treatment of nerve injuries. Further, stem cells sources sharing the same embryological origin as Schwann cells might be considered a suitable tool. The aim of this study was to demonstrate the ability of a neuroectodermal subpopulation of human STRO‐1 + /c‐Kit + /CD34 + DPSCs, expressing P75 NTR, nestin and SOX‐10, to differentiate into Schwann cell‐like cells in vitro and to promote axonal regeneration in vivo, which led to functional recovery as measured by sustained gait improvement, in animal rat model of peripheral nerve injury. Transplanted human dental pulp stem cells (hDPSCs) engrafted into sciatic nerve defect, as revealed by the positive staining against human nuclei, showed the expression of typical Schwann cells markers, S100b and, noteworthy, a significant number of myelinated axons was detected. Moreover, hDPSCs promoted axonal regeneration from proximal to distal stumps 1 month after transplantation. This study demonstrates that STRO‐1 + /c‐Kit + /CD34 + hDPSCs, associated with neural crest derivation, represent a promising source of stem cells for the treatment of demyelinating disorders and might provide a valid alternative tool for future clinical applications to achieve functional recovery after injury or peripheral neuropathies besides minimizing ethical issues. Copyright © 2016 John Wiley & Sons, Ltd.